Wednesday

April 16, 2014

April 16, 2014

Posted by **Sabrina** on Friday, September 24, 2010 at 10:11pm.

SO what am I supposed to do, add the exponents then multiply -2t by 3t? Geez this is so confusing. If I square everything inside the first parentheses by 2 I get (4t^2)

the second parentheses would be (

(9t^9) ?

then it should be 36t^11?

- Math Uugghhh -
**Reiny**, Friday, September 24, 2010 at 10:16pm(-2t)^2(3t^7)^2

= (4t^2)(9t^14)

= 36t^16

just follow the rules you learned

**Related Questions**

Calculus - Simplify. State the nonpermissible values. (3t^2+3t-6/2t^2-2t-4)(4t^2...

Algebra II - Our current assignment is to find the LCM, Least Common Multiple of...

calculus - Let f(t)=2tē+3t-4 f(t+1)=f(t)+4t+5 TRUE or FALSE answer is true, but ...

Algebra - HELP! an object moves in a straight line given by s=2x^2-3t where s is...

calculus/Trig - Suppose you wish to express sin(3t) in terms of sint and cost. ...

College Mathematics. 3 - (3t+1)/5=(t+7)/10+(t-5)/10 I solved this question ...

CALCULUS - Let the line l0 be defined by x = 1−t, y = 2+3t, z = 1−2t...

Algebra - Multiply: (-3t)^2(2t^6)^3

Calculus 12th grade. - 1. A body is moving along a straight line with a velocity...

Pre Calc - |2t-3| = |2t| - |3t| ( || = Absolute Value) I squared both sides to ...